UMP, Yayasan UMP, RDA and Tanjung Lumpur Equestrian Club seal collaboration on equestrian activities - Nor Salwana, Mohammad Idris (UMPSA, 2023)
PEKAN, 15 March 2023 - Universiti Malaysia Pahang (UMP), Yayasan UMP, Riding For The Disabled Association Malaysia (RDA) and Tanjung Lumpur Equestrian Club signed a partnership in equestrian activities through sharing expertise, volunteerism and equestrian services to help children with special needs by providing therapy for them to recover.